Differences in complications, cardiovascular risk factor, and diabetes management among participants enrolled at veterans affairs (VA) and non-VA medical centers in the glycemia reduction approaches in diabetes: A comparative effectiveness study (GRADE). (February 2022) - Florez, Hermes J.; Ghosh, Alokananda; Pop-Busui, Rodica; Hox, Sophia H.; Underkofler, Chantal; McKee, M. Diane; Park, Jean; Rhee, Mary K.; Killean, Tina; Krause-Steinrauf, Heidi; Aroda, Vanita R.; Wexler, Deborah J.; et al.
Highlights: GRADE enrolled participants with type 2 diabetes treated with metformin enrolled at VA and non-VA clinical centers. Participants enrolled at VA and non-VA centers had different baseline characteristics and risk factor management. These differences reflected the background population and management protocols prevalent at these two categories of clinical centers. VA participants had similar HbA1c and weight as non-VA participants. VA participants had higher rates of hypertension, hyperlipidemia, and cardiovascular disease compared to non-VA participants. VA site participants were generally more likely than non-VA participants to have guideline-concordant CVD risk factor management. Abstract: Aims: We evaluated differences in participants with type 2 diabetes (T2DM) enrolled in the GRADE study at VA vs non-VA sites, focusing on cardiovascular risk factors and rates of diabetes care target achievements. Methods: We compared baseline characteristics between participants at VA (n = 1216) and non-VA (n = 3831) sites, stratifying analyses by cardiovascular disease (CVD) history. Results: VA and non-VA participants had similar diabetes duration (4.0 years), HbA1c (7.5%), and BMI (34 kg/m 2 ); however, VA participants had more individuals ≥ 65 years (37.3% vs 19.8%, p < 0.001), men (90.0% vs 55.2%, p < 0.001), hypertension (75.8% vs 63.6%, p < 0.001), hyperlipidemia (76.6% vs 64.6%, p < 0.001), current smokers (19.0% vs 12.1%, p < 0.001), nephropathy (20.4% vs 17.0%, p < 0.05), albuminuria (18.4% vs 15.1%, p < 0.05), and CVD (10.4% vs 5.2%, p < 0.001). In those without CVD, more VA participants were treated with lipid (70.8% vs 59.5%, p < 0.001) and blood pressure (74.9% vs 65.4%, p < 0.001) lowering medications, and had LDL-C < 70 mg/dl (32.9% vs 24.2%, p < 0.05). Among those with CVD, more VA participants had BP < 140/90 (80.2% vs 70.1%, p < 0.05) after adjusting for demographics. Conclusion: GRADE participants at VA sites had more T2DM complications, greater CVD risk and were more likely to be treated with medications to reduce it, leading to more LDL-C at goal than non-VA participants, highlighting differences in diabetes populations and care.